A comparative study on microwave and routine tissue processing - T Mahesh Babu; N Malathi; K T Magesh (Wolters Kluwer Medknow Publications, 2011)
Aim and Objective: The present study was aimed at assessing the rapid microwave-assisted tissue processing and staining to determine if it can replace standard formalin-fixed and paraffin-embedded processing and staining technique. Materials and Methods: The study group consisted of 15 oral mucosal biopsies. The specimens were fixed in 10% formalin for 24 hours to ensure adequate fixation and their gross features were recorded, photographed, and then the specimens were cut into equal halves to be processed by both conventional and microwave histoprocessing methods and then subsequently stained with H and E by microwave and conventional methods. The stained slides in each group processed by both microwave and routine methods were randomly numbered for a blind study and circulated among six observers. All the observers were asked to grade each parameter into Excellent/Good/Average/Poor in a data sheet comprising a total of six parameters. These gradings were given a numerical value of 4, 3, 2 and 1, respectively. The parameters included in the data sheet were cellular clarity, cytoplasmic details, nuclear details, color intensity, interface of epithelium and connective tissue. Wilcoxon-matched pairs signed rank test (non-parametric) was used to calculate the test of significance (P value). Results: The total processing time involved in microwave was 42 minutes and 270 minutes for the conventional method. H and E staining in microwave took 33 minutes and 40 minutes for conventional method. Conclusions: The individual scores by different observers regarding the various parameters included in the study were statistically insignificant, the overall quality of microwave-processed and microwave-stained slides appeared slightly better than conventionally processed and stained slides.